2019
DOI: 10.1186/s40425-019-0597-x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pseudogout after therapy with immune checkpoint inhibitors: a case report with immunoprofiling of synovial fluid at each flare

Abstract: Background Despite ground-breaking clinical success in the treatment of different cancers, immune checkpoint inhibitors can cause profound inflammatory and immune-related adverse events. Autoimmune inflammatory arthritis following immune checkpoint inhibitor treatment has been reported; however, to date, no cases of crystal arthritis following immune checkpoint inhibitors have been identified. Case presentation We report the first case of recurrent pseudogout, an inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“… 79 The first observation of recurrent pseudogout flares 7 to 10 days after each nivolumab infusion has been recently reported. 80 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 79 The first observation of recurrent pseudogout flares 7 to 10 days after each nivolumab infusion has been recently reported. 80 …”
Section: Resultsmentioning
confidence: 99%
“…79 The first observation of recurrent pseudogout flares 7 to 10 days after each nivolumab infusion has been recently reported. 80 Several cases of myositis have been reported, with frequent limb-girdle myalgia and weakness that may mimic a PMR-like condition. [81][82][83] Because it represents a potentially life-threatening complication, the task force decided to formulate a dedicated recommendation on myositis (recommendation 8).…”
Section: Points To Considermentioning
confidence: 99%
“…63 Whether colchicine has the potential to reduce ICIassociated atherosclerosis is currently unknown, but it has been reported that colchicine prevented recurrent ICI-associated inflammatory arthritis in a patient who received the PD1 inhibitor nivolumab for renal cell carcinoma. 64 The well-known and favorable safety profile, oral availability and inexpensiveness may further increase the clinical applicability of this drug.…”
Section: Open Accessmentioning
confidence: 99%
“…There are reports of patients experiencing "activated OA," with more pain and swelling at joints previously affected by OA (11,18). Crystalline arthritis, particularly calcium pyrophosphate disease (19,20), was also reported in patients being treated with ICIs. We ask patients about all past musculoskeletal, inflammatory, and autoimmune diagnoses, with particular attention to prior injuries and surgeries, OA, and crystalline arthritis.…”
Section: Approachmentioning
confidence: 99%